2005
DOI: 10.1002/pmic.200401289
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art in phosphoproteomics

Abstract: Presently, phosphorylation of proteins is the most studied and best understood PTM. However, the analysis of phosphoproteins and phosphopeptides is still one of the most challenging tasks in contemporary proteome research. Since not every phosphoprotein is accessible by a certain method and identification of the phosphorylated amino acid residue is required in the majority of cases, various strategies for the detection and localization of phosphorylations have been developed. Identification and localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
255
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(256 citation statements)
references
References 97 publications
(95 reference statements)
0
255
0
1
Order By: Relevance
“…Phosphorylation is a key regulator of intracellular biological processes and at present, it is the most studied and best understood PTM [1,2]. Protein phosphorylation is known to be involved in the regulation of diverse processes including metabolism, transcriptional, and translational regulation, degradation of proteins, homeostasis, cellular signaling and communication, proliferation, differentiation, and cell survival [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation is a key regulator of intracellular biological processes and at present, it is the most studied and best understood PTM [1,2]. Protein phosphorylation is known to be involved in the regulation of diverse processes including metabolism, transcriptional, and translational regulation, degradation of proteins, homeostasis, cellular signaling and communication, proliferation, differentiation, and cell survival [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic sequencing has revealed that 2-3% of all eukaryotic genes are likely to code for protein kinases [6] and more than 100 human protein phosphatases have been predicted by genome annotation [7], emphasizing the ubiquitous role of protein phosphorylation. At present, no studies have been able to elucidate how many proteins are in fact regulated by phosphorylation, but it has been estimated that more than 50 percent of all proteins are phosphorylated during their lifetime [2], and that more than 100 000 phosphorylation sites may exist in the human proteome [8]. Despite its ubiquitous role, phosphoproteins are generally present at relatively low abundance within the cell and phosphorylated forms of individual proteins also tend to be present at much lower ratios than their native counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…We also report that such neutral losses may be reduced by fragmenting peptide-alkali metal adducts, such as sodiated or potassiated peptides. (J Am Soc Mass Spectrom 2007, 18, 1617-1624) © 2007 American Society for Mass Spectrometry P hosphopeptides are the most frequently targeted post-translational modifications in proteomics studies because of their biological significance [1][2][3][4][5]. Sulfopeptides also display an 80 Da mass increase as well as similar chromatographic and mass spectrometric behavior [6].…”
mentioning
confidence: 99%
“…However, the amount of phosphorylated proteins in eukaryotic cells often exists in substoichiometry level, which makes the identification of phosphorylation sites challenging [3]. To date, mass spectrometry (MS) analysis has become an effective and commonly used method for characterization of phosphoproteins [4].…”
Section: Introductionmentioning
confidence: 99%